KNITTING UNITY THROUGH TONE: STRENGTHENING NATIONALISM THE NATION'S CHILDREN THROUGH THE ART OF SOUND - Batubara, Junita; Marbun, Juliaster; Parulian, Parulian; Sihombing, Jenny Ria; Nopelin, Nancy; Sinaga, Dearlina; Elfrida, Rotua (LPPM Univ. Ibn Khaldun Bogor, 2025)
The 2025 Solo Vocal Competition and National Choir organized by Ombas Arts Indonesia is a tangible form of community service that integrates sound arts with character education and strengthening nationalist values. Through the active participation of children aged 9-14 years from various regions, this activity aims to instill the spirit of nationalism, strengthen cultural identity, and shape the character of the younger generation through meaningful musical expression. This activity is designed as an educational and inclusive space, where vocal art is used as a medium of social and emotional learning. This article examines the background of the activity, the implementation method, as well as the results and social impact on the participants and the surrounding community. The analysis was conducted with an art-based character education approach and supported by academic literature and community-based art practices. The results of the study show that art activities such as national vocal competitions are able to strengthen the love of the homeland, increase children's confidence, and build social cohesion between participants and supporting institutions. This article recommends the development of similar activities as a sustainable strategy in character education and art service to the community.